Risk Factors for Stress Fractures in Athletes - Minda, Aleksandra; Zapalska, Barbara Anna; Witkowska, Antonina Teresa; Piotrowska, Julia; Łubińska-Kowalska, Aleksandra; Domańska, Adrianna; Witkowska, Adrianna; Wendland, Monika; Długosz, Krzysztof Julian; Janikowska, Justyna (Quality in Sport, 2025)
Introduction Stress fractures can affect up to 10% of athletes, with amateurs who exhibit high levels of ambition being particularly at risk. This vulnerability is primarily due to their limited understanding of training principles and the physiological mechanisms of the body. Stress fractures result from prolonged, repetitive overload, which leads to the weakening of bone tissue and, consequently, bone fracture. Aim of the study The aim of this review article is to present the current state of knowledge regarding the risk factors for stress fractures in athletes. Materials and Methods This review is based on a literature search conducted on PubMed. The following keywords were used: stress fractures, risk factors, athletes Conclusions Stress fractures primarily result from excessive bone loading that exceeds the bone's ability to repair microdamage caused by daily activities. The mechanism of their formation is complex and related to an insufficient bone response to increased biomechanical demands. Although the causes can be diverse, several key factors are typically associated with the occurrence of these injuries. These include: improper type and intensity of training, female gender, low bone mineral density, nutritional deficiencies, prior stress fractures, and high and low BMI.